2021
DOI: 10.1042/bcj20210211
|View full text |Cite
|
Sign up to set email alerts
|

A home run for human NaCT/SLC13A5/INDY: cryo-EM structure and homology model to predict transport mechanisms, inhibitor interactions and mutational defects

Abstract: NaCT (SLC13A5) is a Na+-coupled transporter for citrate, which is expressed in the liver, brain, testes, and bone. It is the mammalian homolog of Drosophila INDY, a cation-independent transporter for citrate, whose partial loss extends lifespan in the organism. In humans, loss-of-function mutations in NaCT cause a disease with severe neurological dysfunction, characterized by neonatal epilepsy and delayed brain development. In contrast with humans, deletion of NaCT in mice results in a beneficial metabolic phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Citrate is required both as a precursor for de novo fatty acid (FA) synthesis and for the activation of acetyl-CoA carboxylase, the committed step of the pathway [19,20]. SLC13A5 is expressed broadly in the plasma membrane of cells in the brain, testis, kidney, liver, bones, and adrenal gland, with enriched expression in hepatocytes along the sinusoidal membrane [10,19,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Citrate is required both as a precursor for de novo fatty acid (FA) synthesis and for the activation of acetyl-CoA carboxylase, the committed step of the pathway [19,20]. SLC13A5 is expressed broadly in the plasma membrane of cells in the brain, testis, kidney, liver, bones, and adrenal gland, with enriched expression in hepatocytes along the sinusoidal membrane [10,19,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The current knowledge for the structural basis of the NaCTs is based upon Vibrio cholerae bacterial dicarboxylate transporter VcINDY. The structure VcINDY greatly differs from the human NaCT but still acts as the best option for the modeling studies [11]. It has a total of 11 transmembrane (TM) helices hairpin loops marked as HP in (hairpin in) and HP out (hairpin out).…”
Section: Structural Composition Of Nactmentioning
confidence: 99%
“…Although Slc13A5 null mice show some neurological abnormalities, neurological dysfunction does not seem to be present in mice to the same extent [ 18 ]. Based on these different effects of NaCT deficiency in the brain and the periphery, it has been suggested that NaCT inhibitors that do not permeate the blood-brain barrier could have advantages [ 19 ]. It may thus be prudent to avoid complete and sustained NaCT blockade when applying brain-permeable NaCT inhibitors.…”
Section: Introductionmentioning
confidence: 99%